2007
DOI: 10.1177/1524838007307593
|View full text |Cite
|
Sign up to set email alerts
|

Resistance, Reluctance, and Readiness in Perpetrators of Abuse Against Women and Children

Abstract: Perpetrators of abuse and violence against women and children are often reluctant participants in intervention programs. They frequently fail to attend scheduled appointments, are sometimes openly hostile to intervention staff, and often judge program materials as irrelevant to their situation. Recognizing this problem, researchers and practitioners have begun to develop models and tools to more appropriately assess and intervene with reluctant clients. Unfortunately, the resulting proliferation and inconsiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 70 publications
0
42
0
2
Order By: Relevance
“…101 While creating behavior change in men who have longestablished patterns of abusive behavior is extraordinarily challenging even in court-mandated programs, reaching men who are less controlling, have more insight and motivation to change, or are very early in the development of abusive behavior may be possible. 102,103 Identifying IPV perpetration as a health-care issue, modeling respectful behavior, and expressing concern for the health and well-being of a perpetrator allow providers to encourage men to change in a non-judgmental manner.…”
Section: Controversy Over Ipv "Screening" and Rationale For Addressinmentioning
confidence: 99%
See 1 more Smart Citation
“…101 While creating behavior change in men who have longestablished patterns of abusive behavior is extraordinarily challenging even in court-mandated programs, reaching men who are less controlling, have more insight and motivation to change, or are very early in the development of abusive behavior may be possible. 102,103 Identifying IPV perpetration as a health-care issue, modeling respectful behavior, and expressing concern for the health and well-being of a perpetrator allow providers to encourage men to change in a non-judgmental manner.…”
Section: Controversy Over Ipv "Screening" and Rationale For Addressinmentioning
confidence: 99%
“…Research and detailed observation of male perpetrators have demonstrated that they routinely deny their violent behavior, minimize the severity of their violent actions and the effects of their violence, and blame the violence on others. 103,110 Perpetrators of IPV may be so manipulative and present themselves so convincingly as victims that it is extremely challenging for health-care providers (or other such as judges, law enforcement officers, etc.) to suspect or understand the extent of their abusive behaviors.…”
Section: Distinguishing Ipv Victimization From Ipv Perpetration In Mamentioning
confidence: 99%
“…Engagement is more than merely attending for help (Scott & King 2007). It refers to the extent to which SUs actively participates in their care (Tetley et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The little research that exists on responsivity has mostly focused on the programme or process factors that enhance treatment outcomes (Marshall, Marshall, & Burton, 2013), such as the use of social learning principles, the importance of therapeutic alliance (Kozar & Day, 2012;Watson, Daffern, & Thomas, 2015), and effective strategies for programme delivery (Marshall & Marshall, 2012). Limited research has focused on whether, and how individual offender characteristics influence the effectiveness of violence intervention programmes (Scott & King, 2007). Although numerous internal offender characteristics have been highlighted as possible barriers to treatment participation (e.g.…”
Section: Understanding Responsivitymentioning
confidence: 99%